INFLUENCE OF ORGANIZATIONAL CLIMATE AND JOB SATISFACTION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR MEDIATED BY MOTIVATION VARIABLES - Murwidiastomo, Bagas (Dinasti International Journal of Digital Business Management, 2021)
The success of an organization is largely determined by its employees, not only because of their abilities and competencies but also the personality values that employees apply in carrying out their work. Perum Jasa Tirta II (PJT II) has the task of servicing and guaranteeing the availability of water to fulfill the interests of water resource exploitation while still prioritizing the fulfillment of water needs for daily basic needs and irrigation for smallholder agriculture in the existing irrigation system. To serve the fulfillment of agricultural needs, employees are expected to work and contribute optimally. For this reason, organizational citizenship behavior (OCB) or the willingness of employees to contribute in their work even beyond the demands of the role is needed. This study aims to determine the effect of organizational climate and job satisfaction on OCB which is mediated by motivational variables. This study uses a quantitative approach with data analysis in testing the measurement model and testing the structural model using SmartPLS software version 3.2.7. The results of the study reveal that organizational climate has a significant positive effect on motivation and OCB. Job satisfaction has a significant positive effect on motivation but does not have a significant positive effect on OCB. Organizational climate and job satisfaction simultaneously have a positive and significant effect on motivation. In addition, motivational variables mediate organizational climate and job satisfaction on OCB.